A Turn to Engineering: The Continuing Struggle of Technology Education for Legitimization as a School Subject - Lewis, Theodore (Journal of technology education, 2004)
In the long march from manual training, the subject which today is called technology education has always had to contend with the question of its legitimacy as valid school knowledge. In this regard, it shares a similar history of struggle with other subjects whose initial entry into the curriculum was based on a utilitarian rather than an academic rationale. At its origins, the subject of technology was premised upon blue-collar knowledge. The content was derived from the practices of crafts-people--blacksmiths, machinists, and cabinet-makers. The intent of early advocates was not for this knowledge to be used to reproduce the blue-collar classes that invented it, by teaching it to their children exclusively. Rather, it was legitimate education that would be valid for all children. In this paper the author examines the phenomenon of pre-engineering as the most recent claimant to the technology education tradition, and argues that pre-engineering is the latest evidence of a decided turn away from the blue-collar traditions of the field, toward white-collar academic traditions.